Optimasi Adsorpsi Ion Logam Cu2+ dengan Menggunakan Cangkang Telur Ayam Ras - Nesya Febi Utami; Edi Nasra; Desy Kurniawati; Umar Kalmar Nizar (Jurnal Periodic Jurusan Kimia UNP, 2022)
adsorption is a method of waste treatment that has the potential to remove toxic heavy metals. One of the factors that influence the occurrence of the adsorption process is the presence of a biological material called a biosorbent. The adsorption method is a method of absorbing heavy metal contamination in liquid waste that is very efficient and effective, as well as easy and cheap economically because of the use of biomaterials that are very cheap and can be regenerated. Chicken egg shell contains Calcium Carbonate (CaCO3) of 98.41% and has natural pores of 10,000 to 20,000 so it is estimated that it can absorb solutes. Based on the known mineral composition, chicken egg shells are composed of CaCO3 (98.41%), Ca3(PO4)2 (0.75%), and MgCO3 (0.84%). So it can be seen that chicken egg shells have a high calcium carbonate content, where calcium carbonate is a polar adsorbent. The optimum conditions for each variable in contacting broiler egg shells that have been activated with Cu2+ metal ions are optimum at pH 4, concentration of 250 ppm.